MODERN APPROACHES OF DISSOLUTION PROFILE TEST (REVIEW) - D. Yu. Grebenkin; Ya. M. Stanishevskiy; I. E. Shohin (Разработка и регистрация лекарственных средств, 2019)
Modern approaches of dissolution profile test were reviewed in terms of documents, research design, principles of choice of test conditions, selection and validation of assay methods, results evaluation and technique of the carrying out of experiment directly. The article reflects both Russian and foreign perspectives on dissolution profile test.